PENINGKATAN KREATIVITAS MELALUI METODE MERONCE PADA ANAK DI TAMAN KANAK-KANAK CITA SAHABAT MULIA PONTIANAK - Erna Yunita; M. Syukri; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2021)
AbstractThis research is motivated by a lack of creativity in children aged 5-6 years in a class of 15 children with 2 teachers. This study aims to increase children's creativity through the meronce method for children aged 5-6 years at Cita Sahabat Mulia Kindergarten, Southeast Pontianak. Creativity is very important for everyone to develop themselves optimally. With creativity, someone can use his ideas to create new creations for survival, therefore creativity needs to be increased from an early age. This research is an Action Research). Subjects in this study were children aged 5-6 in group B years at Cita Sahabat Mulia Kindergarten, Southeast Pontianak. The research variable is children's creativity. The research stages consisted of planning, acting , observing, and reflecting. This research was conducted in 2 cycles. The results showed that children's creativity could increase after being given the action. As for the action that will be given is ronce. Children's creativity increases in the aspect of children's fluency in expressing ideas ( fluency ) reaching 87%, the aspect of children's flexibility in developing their ideas (Flexibility ) reaches 80%, and the aspect of authenticity of children in producing works ( originality ) reaches 87% in the second cycle of meeting 2. Thus, children's creativity can be increased through the art of meronce.Keywords: Increased Creativity, Meronce Method, Cita Sahabat Mulia Kindergarten